Prenatal smoking and age at menarche: influence of the prenatal environment on the timing of puberty - Behie, Alison (My University, 2015)
STUDY QUESTION Do prenatal exposure to cigarette smoking and birthweight influence age at menarche (AAM) in a cohort of Australian girls? SUMMARY ANSWER We find that prenatal smoke exposure and lower birthweight increase the chance of earlier menarche in accordance with theoretical predictions as do confounding factors of maternal AAM and higher BMI of the girls. WHAT IS KNOWN ALREADY Much prior research focuses on the role of the early childhood environment in determining AAM but fewer studies consider the role of the prenatal environment. Those studies that examine the prenatal period find an acceleration of maturation associated with maternal smoking and low birthweight. Life history theory predicts that early life exposure to stressful environments should promote more rapid maturation and that this timing can be established before birth, making the prenatal environment particularly important. STUDY DESIGN, SIZE, DURATION Statistical analysis of longitudinal survey data collected from a large cohort (n = 2446) of Australian children using data from birth to 12–13 years of age. PARTICIPANTS/MATERIALS, SETTING, METHODS Owing to missing data, 1493 girls were included in the final analysis. Using cox regression, we examine how (i) maternal cigarette smoking during gestation and (ii) birthweight influence girls' AAM. Cox regression was used because not all girls had reached menarche. MAIN RESULTS AND THE ROLE OF CHANCE We find that older maternal AAM (hazards ratio (HR): 0.75, confidence interval (CI) (95%): 0.71–0.79) and higher birthweight (HR: 0.86, CI (95%): 0.75–0.97) lower the chance of earlier menarche; while higher girls' BMI at 8–9 years (HR: 1.12, CI (95%): 1.10–1.15), and maternal cigarette smoking on ‘most days’ during gestation (HR: 1.40, CI (95%): 1.10–1.79 with ‘no smoking’ as the reference level) increased the chance of earlier menarche. All factors were statistically significant at P = 0.05. LIMITATIONS, REASONS FOR CAUTION Not all girls had reached menarche, necessitating the use of cox regression. As with other longitudinal studies, there was study sample attrition and some missing data, particularly in reports of maternal smoking. In addition, as the degree of bias in the missing data is unknown, possible inaccurate reporting of maternal smoking may influence the results of birthweight on AAM. WIDER IMPLICATIONS OF THE FINDINGS Because of the association between younger AAM and higher risk of uterine, endometrial and breast cancer development, our finding adds to the need to consider the stress caused by prenatal smoke exposure as an important health risk. In addition, this study needs to be extended, when the same girls are 14–15 years of age, and on a larger dataset from a younger cohort within the same Australian Government project.
Human Reproduction
Keywords: Children -- Outcomes; Families -- Mothers; Child Development; Gender -- Female; Childhood and child development; Families and relationships; Gender; Child Development; Children; Gender; Families; Outcomes; Mothers; Female; Gender; Families and relationships; Childhood and child development